Course Director and Academic Sucess: a strategy developed in a Polytechnic Higher Education Institution - Jorge, Susana (2021)
The course director of a higher education institution, within the scope of his/her functions, have a fundamental role in the representation and organization of the course. It is part of his/her competences the coordination of the rules and methodologies of evaluation and the study plan - an example of this is the activities program. Bearing in mind the broadness of its functions, it is important to highlight its role in monitoring the student’s formative path in coordination with other services of the educational institution, namely, the organic units and the institutional offices. The analysis of the academic performance in higher education institutions helps the identification of factors that can be obstacles and it helps in the definition of measures that contribute to the success and social and cultural integration of the students. The course director also has a central role in this process. Given the experience and daily challenges faced in fulfilling the role of a course director in a polytechnic higher education institution, this paper proposes a reflection on what defines a course director, what are his/her goals, how to act in a student environment and in an academic context that constantly changes and demands new measures? We’ll also address another relevant issue: how can the course director’s actions contribute to the students’ academic achievement?